The Effect of Copper(II) and Cadmium(II) Ions Against the Percent Mercury Ion Extraction Using Emulsion Liquid Membrane Technique - Suhartini Musa; Baharuddin Hamzah; Daud K. Walanda (Jurnal Akademika Kimia, 2019)
The effect of copper(II) and cadmium(II) ions on the percent of mercury ion extraction using an emulsion liquid membrane technique have been performed. This study used HNO3 as an internal phase, mixed span 80 and span 20 as a surfactant, benzoyl acetone as cation carrier, kerosene as membrane phase, and mercury solution as a sample solution. Variations of concentrations of copper(II) and cadmium(II) ions added were 10, 20, and 30 ppm with mercury concentrations of 30 ppm. The result of the research showed that the addition of copper(II) ion with concentrations of 10 to 30 ppm decreased the percentage of mercury ion extraction 30 ppm by 12.12% and the addition of cadmium(II) ion with the concentration of 10 to 30 ppm decreased the percentage of mercury ion extraction 30 ppm by 11.74%.